2022
DOI: 10.1021/acsanm.2c03031
|View full text |Cite
|
Sign up to set email alerts
|

Hollow ZnCdS and NiCoP Nanostructures for Photocatalytic Hydrogen Generation

Abstract: To promote photocatalytic reactions and sustain structural stabilities, nanostructured photocatalysts, particularly in hollow and/or framelike forms, have attracted great attention. The photocatalysts with hollow or framelike structures possess advantageous features for photocatalytic reactions with an enlarged accessible surface area, promoted light-response capability, and shortened charge-transfer distance. Here, two fresh hollow-structured nanomaterials, cubiclike ZnCdS (H-ZCS) and NiCoP (H-NCP) frameworks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 56 publications
0
10
0
Order By: Relevance
“…3d, Ni 2p is located at 853.15 eV, assigned to Ni + in NiCoP. [52][53][54] Meanwhile, the peaks located at 856.45 and 874.7 eV is attributed to Ni 2p 1/2 and Ni 2p 3/2 , respectively, while the two peaks at 860.1 eV and 880.25 eV are assigned to nickel satellite peaks. [55][56][57] The existence of Ni 2+ is mainly ascribed to the surface partial oxidation before sample testing.…”
Section: Resultsmentioning
confidence: 99%
“…3d, Ni 2p is located at 853.15 eV, assigned to Ni + in NiCoP. [52][53][54] Meanwhile, the peaks located at 856.45 and 874.7 eV is attributed to Ni 2p 1/2 and Ni 2p 3/2 , respectively, while the two peaks at 860.1 eV and 880.25 eV are assigned to nickel satellite peaks. [55][56][57] The existence of Ni 2+ is mainly ascribed to the surface partial oxidation before sample testing.…”
Section: Resultsmentioning
confidence: 99%
“…Given that the S-scheme and type-II heterojunctions have completely different carrier migration pathways, ISIXPS characterization has been extensively adopted for differentiating these two types of heterojunctions. 65 For example, Xu et al reported an SnO 2 /Cs 3 Bi 2 Br 9 (SC4) S-scheme heterojunction via the electrostatic self-assembly of SnO 2 nanofibers and leadfree Cs 3 Bi 2 Br 9 quantum dots (QDs). 66 In situ XPS under light and dark conditions was performed to determine the charge transfer mechanism (Fig.…”
Section: Isixpsmentioning
confidence: 99%
“…Compared with Co 9 S 8 and Ni 2 P, CSNP-2 shows a stronger photocurrent density, which means that CSNP-2 has a relatively low carrier recombination rate, indicating that the prepared CSNP-2 heterojunction material has a more efficient carrier separation and migration rate. 68 The electrochemical impedance spectra of the three catalysts are shown in Fig. 6b.…”
Section: The Photoelectrochemical Characterization Testmentioning
confidence: 99%